The Dilemma of the Honorary Employee Elimination Policy: An Analysis of Good Governance and its Impact on Public Services in South Tangerang City - Syaiful Amin; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The policy on restructuring non-civil servant personnel as regulated in Law Number 20 of 2023 on State Civil Apparatus (ASN) has significant implications for public sector human resource governance at the local level. A case study in South Tangerang reveals that approximately 1,800 honorary workers were laid off and faced income uncertainty due to the absence of legal budgeting frameworks, failure in PPPK selection, and administrative constraints. This situation potentially disrupts public service delivery, particularly in the health sector. This study aims to analyze the governance of non-permanent employee restructuring from a public administration perspective and its impact on public services. The research employs a qualitative descriptive approach using a case study method, based on policy document analysis and empirical observation. The analytical framework draws upon Good Governance, New Public Service, and Public Value theories. The findings indicate that policy implementation has not fully met Good Governance principles, particularly in transparency, accountability, and regulatory effectiveness. Consequently, public service disruption and declining public trust have emerged. The study recommends adaptive transition policies, strengthened intergovernmental coordination, and protection mechanisms for affected workers.